Office‐based 532‐Nanometer pulsed potassium‐titanyl‐phosphate laser for marsupialization of laryngeal and vallecular mucoceles. (20th July 2016) - Helman, Samuel N.; Pitman, Michael J.
Abstract : Objectives/Hypothesis: Many laryngopharyngeal disorders are effectively managed in the office. Herein, an in‐office method utilizing the 532‐nm potassium‐titanyl‐phosphate (KTP) laser for the treatment of benign laryngeal and vallecular mucoceles is described. Study Design: Retrospective case review. Methods: A review was performed of patients who had their vallecular or laryngeal mucoceles marsupialized in the office using KTP laser. Results: Outcomes included long‐term follow‐up laryngoscopy for evidence of recurrence, significant intraprocedural complications, tolerance of the procedure, final pathology of the specimen, and resolution of symptoms. Conclusions: In‐office KTP marsupialization of laryngeal and vallecular mucoceles is effective and well tolerated, with no episodes of recurrence to date. Level of Evidence: 4. Laryngoscope, 127:1116–1118, 2017